Youth Unemployment in Advanced Economies in Europe : Searching for Solutions - Banerji, Angana (Staff Discussion Notes; Staff Discussion Notes ;, 2014)
The SDN will assess the youth unemployment problem in advanced European countries, with a special focus on the euro area. It will document the main trends in youth and adult unemployment in 22 European countries before and after the global financial crisis. It will identify the main drivers of youth and adult unemployment, focusing in particular on the role of the business cycle and structural characteristics of the labor market. It will outline the main elements of a comprehensive strategy to address the problem.